(untitled) (UNIHumanitas, 2020)
This research called: Theory of Realism and the Government of Doctor Francia, has as general objective: To determine the role played by the theory of realism in the international management of the Government of Doctor José Gaspar Rodríguez de Francia. And the specific objectives: to describe the role played by realism in International Relations, and; to identify the decisional facts practiced by Doctor Francia that are subsumed with the theory of the classic realism of International Relations. The research level was descriptive and the approach was qualitative. An exhaustive analysis of the arguments and the theories found was carried out; the description of the role played by realism in international relations, as well as the identification of the decision-making facts practiced by Dr. Francia that are compatible with the theory of classical realism in International Relations. The main conclusions were: it was determined that the theory of realism has played a fundamental role in the international management of the Government of Dr. José Gaspar Rodríguez de Francia by necessarily having a base and a support rooted according to Pastor Benítez (2010) in realism, where the Paraguayan State was the actor par excellence in the international community system.